1996
DOI: 10.1165/ajrcmb.15.5.8918367
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of alpha E beta 7 integrins on bronchoalveolar lavage T lymphocyte subsets: regulation by alpha 4 beta 1-integrin crosslinking and TGF-beta.

Abstract: T lymphocytes expressing the alpha E beta 7 integrin are localized and selectively retained in mucosal tissues. To investigate a potential relationship between alpha E beta 7 expression and pulmonary inflammation, the distribution of alpha E beta 7-bearing CD4+ and CD8+ T cells in peripheral blood and bronchoalveolar lavage (BAL) fluids obtained from patients with allergic asthma, sarcoidosis, hypersensitivity pneumonitis, and idiopathic pulmonary fibrosis (IPF) was determined. In contrast to the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
42
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 39 publications
7
42
0
1
Order By: Relevance
“…In previous work we reported that the regulation of CD103 expression differs between CD4 ϩ and CD8 ϩ T cells. Moreover, we and others reported that the proportion of CD103 ϩ T cells in the BAL within the CD4 ϩ T-cell population increases significantly in interstitial lung diseases (8,9).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In previous work we reported that the regulation of CD103 expression differs between CD4 ϩ and CD8 ϩ T cells. Moreover, we and others reported that the proportion of CD103 ϩ T cells in the BAL within the CD4 ϩ T-cell population increases significantly in interstitial lung diseases (8,9).…”
Section: Discussionmentioning
confidence: 64%
“…Although it is expressed on only a small proportion of blood T cells, it is induced upon activation of the T cells in the presence of transforming growth factor (TGF) ␤1 (8,18). In previous work we reported that the regulation of CD103 expression differs between CD4 ϩ and CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations